Robber flies of South Korea IV. Species of the subfamily Stichopogoninae Hardy, 1930 (Diptera: Asilidae) - Young, Charles L. (Zootaxa, 2007)
Two genera and 8 species of the subfamily Stichopogoninae are recorded from South Korea. New records include: Lasiopogon akaishii Hradský, Lasiopogon hasanicus Lehr, Lasiopogon hinei Cole & Wilcox, Lasiopogon leleji Cannings, Lasiopogon rokuroi Hradský, Lasiopogon terneicus Lehr, Stichopogon elegantulus orientalis Lehr, Stichopogon cf. inaequalis Loew and Stichopogon nartshukae Lehr. Both the genera of Lasiopogon Loew and Stichopogon Loew are new records for the area. Drawings of diagnostic features, a checklist, keys, and descriptions of adults are included.